Perspectives on Reprograming Cancer-Associated Dendritic Cells for Anti-Tumor Therapies - Benencia, Fabian; Muccioli, Maria; Alnaeeli, Mawadda (Frontiers in Oncology, 2014)
In recent years, the relevance of the tumor microenvironment (TME) in the progression of cancer has gained considerable attention. It has been shown that the TME is capable of inactivating various components of the immune system responsible for tumor clearance, thus favoring cancer cell growth and tumor metastasis. In particular, effects of the TME on antigen presenting cells, such as dendritic cells (DCs) include rendering these cells unable to promote specific immune responses or transform them into suppressive cells capable of inducing regulatory T cells. In addition, under the influence of the TME, DCs can produce growth factors that induce neovascularization, therefore further contributing to tumor development. Interestingly, cancer-associated DCs harbor tumor antigens and thus have the potential to become antitumor vaccines in situ if properly reactivated. This perspectives article provides an overview of the scientific background and experimental basis for reprogramming cancer-associated DCs in situ to generate anti-tumor immune responses.